The Effect of Innovation, Creativity, and Employee Retention for Human Resource Development in North Sumatra’s Ulos Industry - Junika Napitupulu (Jurnal Ilmiah Manajemen Kesatuan, 2025)
The Ulos woven fabric industry in North Sumatra has faced a significant decline due to limited innovation and outdated designs, impacting business sustainability. This study aims to analyze the influence of innovation and creativity on human resource development in the Ulos industry, with employee retention as an intervening variable. A quantitative descriptive approach was used, collecting data from 294 Ulos business owners through questionnaires. Data were analyzed using structural equation modeling with SMART Partial Least Squares 4.0 software. The findings show that innovation and creativity significantly enhance human resource development by improving employee skills and business performance. Employee retention strengthens this relationship by ensuring skilled workers remain, contributing to sustained development. The study concludes that fostering innovation through new weaving techniques and creativity through unique motif designs can revive the Ulos industry. Business owners should implement training programs and retention strategies, such as fair compensation, to maintain a skilled workforce and enhance product competitiveness, addressing the industry’s decline.